Peran Asuransi Syariah Dalam Mendukung Pertumbuhan Ekonomi di Indonesia - Zahara, Alfiatun; Rahmawati, Rahmawati (EL-EMIR Institute, 2024)
This research aims to investigate the role of sharia insurance in supporting economic growth in Indonesia through a qualitative approach, which includes a comprehensive literature study regarding the concept of economic growth and the application of sharia insurance. Indonesia, as the country with the largest Muslim population in the world, has great potential in developing the sharia economy, including in the sharia insurance sector. Sharia insurance, which is based on the principles of mutual assistance (ta'awun) and risk sharing, offers an alternative for people who want financial protection in accordance with Islamic principles. This research uses a qualitative approach by conducting a comprehensive literature study on economic growth and sharia insurance. The research results show that sharia insurance plays an important role in supporting economic growth in Indonesia. Sharia insurance has made a significant contribution to increasing investment and national financial stability. Apart from that, sharia insurance also helps reduce risks and provides protection for the community. Thus, the rapid development of sharia insurance in Indonesia has had a positive influence on the national economy.